Efeitos da suplementação de fitosteróis à terapia hipolipemiante na hipercolesterolemia familiar - Machado, Valeria Arruda [UNIFESP] (2013)
OBJECTIVES: Familial hypercholesterolemia (FH) is a severe inherited dyslipidemia often requiring high-dose lipid-lowering therapy and combined therapy. Plant sterol supplementation can improve achievement of lipid targets, but their effects on cholesterol synthesis and absorption need evaluation, because increase in phytosterolemia can be associated with a higher cardiovascular risk. We evaluted the effects of plant sterol supplementation to the lipid-lowering therapy with statin or combined with ezetimibe on lipids, markers of cholesterol synthesis and absorption. METHODS: A prospective, randomized, open label study, witl parallel arms and blinded endpoints included 42 individuals of both genders with clinical and/or genetic diagnosis of heterozygous FH (Med Ped, Dutch Lipid Clinics Network, Simon Broome). After a 4- week washout period of the previous lipid-lowering therapy and under NCEP/ATPIII nutrition counseling, the patients were randomized to receive 12 weeks of simvastatin 80 mg or simvastatin 80mg plus ezetimibe 10mg. Further, 2g/day of free phytosterols (Vegapure), were added to the previous treatment for another 12-week period. Lipids, apolipoproteins (Apo), markers of cholesterol absorption (campesterol and ?-sitosterol) and endogenous synthesis (desmosterol) (Ultra Performance Liquid Chromatography/Mass Spectrometry), were assessed at baseline, 12 and 24 weeks. Statistical analysis used parametric or non-parametric tests, as appropriate. RESULTS: The groups were comparable at baseline. Both lipid-lowering therapies effectively reduced total and LDL-c, triglycerides and Apo B (P<0,001 vs. baseline), however, greater modification was observed with the combined therapy (P<0.05 vs. simvastatin (Student?s t-test). Addition of 2g of plant sterols further decreased LDL-c only in the group receiving simvastatin/ezetimibe (P<0.05, paired t-test). Simvastatin plus plant sterols increased campesterol, ?-sitosterol, desmosterol and their ratios to cholesterol (P<0,05), whereas the combined therapy reduced the absorption markers, while preventing the increase in cholesterol synthesis, and also reduced the ratios between sterols and cholesterol (P<0,05). CONCLUSIONS: Addition of phytosterols to lipid-lowering therapies in FH is beneficial on LDL-c only when the treatment includes the cholesterol absorption inhibitor, ezetimibe. Changes on cholesterol synthesis and absorption can influence the results of lipid-lowering interventions.